The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1029/2020sw002660
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Solar Activity on Forecasting the Upper Atmosphere via Assimilation of Electron Density Data

Abstract: • Investigates the impact of solar activity on forecasting through assimilation of COSMIC-N e into a physics-based upper atmosphere model • The agreement between hourly forecasted N e and data is better during solar minimum than solar maximum • The assimilation reduces RMSE of N e estimates much more significantly during the high solar activity period • The assimilation of COSMIC-N e into TIE-GCM significantly influences the neutral dynamics of the thermosphere

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…We also compared TIE-GCM and TIE-GCM-I with RO measurements, which showed that the vertical profiles of the forecasts can be positively improved on average. Previous studies, dealing with the data assimilation of upper atmosphere, already demonstrated the success EnKF-based data assimilation while using TIE-GCM as base model 41 , 79 , 80 . In these studies, however, electron density was used as main observation to tune the model’s skills for estimating ionosphere related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared TIE-GCM and TIE-GCM-I with RO measurements, which showed that the vertical profiles of the forecasts can be positively improved on average. Previous studies, dealing with the data assimilation of upper atmosphere, already demonstrated the success EnKF-based data assimilation while using TIE-GCM as base model 41 , 79 , 80 . In these studies, however, electron density was used as main observation to tune the model’s skills for estimating ionosphere related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We chose NEDM (briefly described in Jakowski & Hoque, 2019) as a representative empirical model. The TIE‐GCM was selected for this comparison since it is a well‐established physics‐based model (Hsu et al., 2021; Kodikara et al., 2021; Qian et al., 2014). TIE‐GCM uses a finite differencing technique to discretize the numerical solutions for the conservation of mass, energy, and momentum to model the coupled ionosphere‐thermosphere (Qian et al., 2014; Richmond et al., 1992).…”
Section: Resultsmentioning
confidence: 99%
“…In future work, it may be beneficial to investigate the performance and efficiency of the global tomography in comparison to regional reconstructions using dense GNSS networks, such as the regional methods applied over Japan (Saito et al., 2017). Data assimilation approaches applied on numerical models (e.g., Hsu et al., 2021; Kodikara et al., 2021) would also be an interesting option for comparison with the global‐scale tomography results. Similarly, the high accuracy tomography outputs could be used to drive the numerical models in forecasting applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a long‐history of lower atmosphere data assimilation (Gelaro et al., 2017; Hersbach et al., 2020; Rienecker et al., 2011), but the whole atmosphere system data assimilation is relatively new. There have been significant developments in the assimilation of thermosphere‐ionosphere observations such as, neutral density (Matsuo et al., 2013; Mehta et al., 2018; M. V. Codrescu et al., 2004; Ren & Lei, 2020; S. M. Codrescu et al., 2018; Sutton, 2018), thermospheric temperature (Laskar, Pedatella, et al., 2021), thermospheric airglow radiance (Cantrall et al., 2019), and electron content (Aa et al., 2016; Bust et al., 2004; Bust & Immel, 2020; Chen et al., 2016; Datta‐Barua et al., 2013; Forsythe et al., 2021; He et al., 2020; Kodikara et al., 2021; Lee et al., 2012; Lin et al., 2015; Matsuo et al., 2013; Pedatella et al., 2020; Song et al., 2021). While these results were promising and showed that the assimilation of TI observations improves the model states, most were limited to using upper atmosphere only models or used limited thermospheric datasets from low‐earth‐orbit satellites or ionospheric only measurements or observing system simulation experiments.…”
Section: Introductionmentioning
confidence: 99%